HIV-1 Nef down-regulates the hemochromatosis protein HFE, manipulating cellular iron homeostasis. - Drakesmith, H; Chen, N; Ledermann, H; Screaton, G; Townsend, A; Xu, X (2005)
The multifunctional Nef protein of HIV-1 is important for the progression to AIDS. One action of Nef is to down-regulate surface MHC I molecules, helping infected cells to evade immunity. We found that Nef also down-regulates the macrophage-expressed MHC 1b protein HFE, which regulates iron homeostasis and is mutated in the iron-overloading disorder hemochromatosis. In model cell lines, Nef reroutes HFE to a perinuclear structure that overlaps the trans-Golgi network, causing a 90% reduction of surface HFE. This activity requires a Src-kinase-binding proline-rich domain of Nef and a conserved tyrosine-based motif in the cytoplasmic tail of HFE. HIV-1 infection of ex vivo macrophages similarly down-regulates naturally expressed surface HFE in a Nef-dependent manner. The effect of Nef expression on cellular iron was explored; iron and ferritin accumulation were increased in HIV-1-infected ex vivo macrophages expressing wild-type HFE, but this effect was lost with Nef-deleted HIV-1 or when infecting macrophages from hemochromatosis patients expressing mutated HFE. The iron accumulation in HIV-1-infected HFE-expressing macrophages was paralleled by an increase in cellular HIV-1-gag expression. We conclude that, through Nef and HFE, HIV-1 directly regulates cellular iron metabolism, possibly benefiting viral growth.